Perspectives on Citizen Science Data Quality - Downs, Robert R.; Ramapriyan, Hampapuram K.; Peng, Ge; Wei, Yaxing (Frontiers in Climate, 2021)
Information about data quality helps potential data users to determine whether and how data can be used and enables the analysis and interpretation of such data. Providing data quality information improves opportunities for data reuse by increasing the trustworthiness of the data. Recognizing the need for improving the quality of citizen science data, we describe quality assessment and quality control (QA/QC) issues for these data and offer perspectives on aspects of improving or ensuring citizen science data quality and for conducting research on related issues.